Energy spectrum and eigenfunctions through the Quantum Section Method - Ortiz, JSE; Carvalho, R. E. de (Sociedade Brasileira Fisica, 2001)
We present the Quantum Section Method as a quantization technique to compute the eigenvalues and the eigenfunctions of quantum systems. As an instructive example we apply this procedure to quantize the annular billiard. The method uses the symmetry of the system to determine an auxiliary section separating the system into partial regions and computes the Green's functions for Schroedinger's equation, obeying the same boundary conditions imposed on the eigenfunctions of the system. The eigenvalues are obtained as zeroes of a finite real determinant and the eigen fu net ions are also determined. The present analytical and numerical results are in total agreement with those. obtained by other procedures, which shows the efficiency of the method.